STRATEGI PENINGKATAN KINERJA PENDIDIK PROFESIONAL BERBASIS ETOS KERJA QUR’ANI - Rosidin, Rosidin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
This paper is the text of the Koran studies aimed at finding Quranic ethos of the key concepts that could potentially improve the quality of professional educators fourth competence, if implemented optimally. In the process, this article refers to the steps of methodological-applicative interpretation Tarbawi practical: to determine the theme, identify the passages relevant, then analyze the data paragraph with three analytical techniques, namely language (lughawi), content (tahlili) and education (Tarbawi ). There are three main findings of this study. First, the